2020
DOI: 10.1098/rsif.2020.0278
|View full text |Cite
|
Sign up to set email alerts
|

Task-level regulation enhances global stability of the simplest dynamic walker

Abstract: Much remains unknown about how considerations such as stability and energy minimization shape the way humans walk. While active neuromotor control keeps humans upright, they also need to choose from multiple stepping regulation strategies to achieve one or more task goals, such as maintaining a desired speed or direction. Experiments on human treadmill walking motivate an important question: why do humans prefer one task-level regulation strategy over another—perhaps to enhance their ability to reject large di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(66 citation statements)
references
References 36 publications
3
63
0
Order By: Relevance
“…The walker admits families of 'long-period' and 'short-period' gaits 6,19 , which are fixed points (θ * , θ * ; P * ) of the map F F F (equation 2), for a given P * . While the long-and short-period gaits admit distinct step times and contrasting open-loop stability as θ + → 0 20 , their curves 17 intersect at (0, 0) in the original state space (Fig. 2a).…”
Section: -Step Viable Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…The walker admits families of 'long-period' and 'short-period' gaits 6,19 , which are fixed points (θ * , θ * ; P * ) of the map F F F (equation 2), for a given P * . While the long-and short-period gaits admit distinct step times and contrasting open-loop stability as θ + → 0 20 , their curves 17 intersect at (0, 0) in the original state space (Fig. 2a).…”
Section: -Step Viable Regionmentioning
confidence: 99%
“…Therefore, the viable region is also the set within which different motor regulation strategies can be meaningfully compared for their effect on the walker's ability to avoid falls. Taking step-to-step speed regulation as a model task-level motor regulation strategy 9,16,17 , we estimate the speed-regulated walker's basins for several target speeds vis-à-vis the viable region. Not only do the speed-regulated walker's basins occupy large regular regions, but we find that only a small collection of these basins covers nearly the entire viable region itself.…”
Section: Introductionmentioning
confidence: 99%
“…Across the life sciences, we encounter systems over which we wish to exert control. Whether we consider outbreak control in epidemiology [1,2], chemotherapy in oncology [3][4][5], muscle contraction and gait regulation in biomechanics [6][7][8], engineering cellular processes in synthetic biology [9,10], cell population growth in tissue engineering [11,12], or biodiversity and invasive species management in ecology [13][14][15], we face decisions around how a particular intervention should be applied to best achieve desired outcomes. Using mathematical models of such systems, optimal control theory provides insight into these resource allocation decisions.…”
Section: Introductionmentioning
confidence: 99%
“…These studies typically solve the dynamics of the SLIP model, then derive a controller to create a closed system model [17][18][19][20]. Beyond this, work with both the inverted pendulum and SLIP models have shown that different controllers can drastically change important gait properties [14,21]. Thus, it is clear that developing an appropriate controller is critical to producing a desired gait.…”
Section: Introductionmentioning
confidence: 99%